Exploring causal correlations between inflammatory cytokines and knee osteoarthritis: a two-sample Mendelian randomization - Zhang, Jiayu; Li, Kexuan; Qiu, Xiuyue (Frontiers in Immunology, 2024)
Objectives: Knee osteoarthritis (KOA) and certain inflammatory cytokines (such as interleukin 1 [IL-1] and tumor necrosis factor alpha [TNF-a]) are related; however, the causal relationship remains unclear. Here, we aimed to assess the causal relationship between 41 inflammatory cytokines and KOA using Mendelian randomization (MR). Methods: Two-sample bidirectional MR was performed using genetic variation data for 41 inflammatory cytokines that were obtained from European Genome-Wide Association Study (GWAS) data (n=8293). KOA-related genetic association data were also obtained from European GWAS data (n=40,3124). Inverse variance weighting (IVW), MR, heterogeneity, sensitivity, and multiple validation analyses were performed. Results: Granulocyte colony-stimulating factor (G-CSF) or colony-stimulating factor 3 (CSF-3) levels were negatively associated with the risk of developing KOA (OR, 0.93; 95%CI:0.89-0.99, P=0.015). Additionally, macrophage inflammatory protein-1 alpha (MIP-1A/CCL3) was a consequence of KOA (odds ratio [OR], 0.72; 95%CI:0.54-0.97, P=0.032). No causal relationship was evident between other inflammatory cytokines and KOA development.This study suggests that certain inflammatory cytokines may be associated with KOA etiology. G-CSF exerts an upstream influence on KOA development, whereas MIP-1A (CCL-3) acts as a downstream factor.